Building the foundations for an organized population-based cervical cancer screening program with primary HPV self-sampling in Catalonia, Spain: findings from a pilot implementation study - Peremiquel-Trillas, Paula; Roura, Esther; Rangel-Sarmiento, Valentina; Morey, Francisca; Font, Rebeca; Carvajal, Maite; Robles, Clàudia; Ibáñez, Raquel; Pijuan, Lara; Tamarit, Lourdes; Cortasa, Dolça; Fernández, Daniel; et al. (Frontiers in Medicine, 2025)
IntroductionAs part of the transition from opportunistic cytology-based screening to an organized, population-based HPV screening program, Catalonia, Spain, launched an implementation pilot in 2021.MethodsThe pilot combined home-based HPV self-sampling with pharmacy-based distribution, coordinated by a screening office using an SMS-based invitation and reminder system, alongside structured follow-up of HPV-positive cases by midwives.ResultsFrom July 2021 to December 2023, 6,355 women seeking cervical cancer screening were invited to participate in HPV self-sampling via SMS, with high participation (80.9%). Among HPV-positive women (11.8%), compliance with triage cytology was high (98.7%), as with colposcopy referrals when indicated (97.2%). CIN2+ detection rates (3.6% overall, 13.1% in HPV-16 positive) aligned with international studies, reinforcing the value of genotype-specific risk stratification and risk-adapted follow-up pathways in our setting. This organized approach facilitated timely case management and demonstrated the feasibility, acceptability, and effectiveness of the model.DiscussionWhile conducted in an opportunistic screening context with a relatively short follow-up time, these findings support HPV self-sampling as an effective primary screening strategy, including women who regularly attend cervical cancer screening, and provide key insights for its scalability within a population-based program, which began its pilot phase in 2024 and is set for full implementation in 2025.